2002
DOI: 10.1021/es011060n
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Polycyclic Aromatic Hydrocarbons, Toxicity, and Mutagenicity from Domestic Cooking Using Sawdust Briquettes, Wood, and Kerosene

Abstract: Smoke samples, in both gas and particulate matter (PM) phases, of the three domestic stoves were collected using U.S. EPA modified method 5 and were analyzed for 17 PAH (HPLC-UV), acute toxicity (Microtox test), and mutagenicity (Amestest). The gas phase of smoke contributed > or = 95% of 17 PAH, > or = 96% of toxicity, and > or = 60% of mutagenicity. The highest emission factor of 17 PAH was from sawdust briquettes (260 mg/kg), but the highest emission of 11 genotoxic PAH was from kerosene (28 mg/kg). PM samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(42 citation statements)
references
References 12 publications
3
38
0
1
Order By: Relevance
“…It is not surprising to see much larger variation in EF PAHs for coal, ranging from 2.0 (anthracite) to 8021 mg/kg (bituminous). 4548 EF P15 for woody materials measured in other countries are mainly for wood logs burned in laboratory chambers, 31, 39, 44, 47 woodstove 18, 36, 3841, 4546, 4951, 54 or fireplace. 18, 3435, 37, 5253 Reported EF P15 values for wood logs burned in laboratory chambers, wood stoves, and fireplaces range from 5.4–35, 1.5–63, and 0.32–332 mg/kg, with geometric means of 15, 8.0, and 16 mg/kg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is not surprising to see much larger variation in EF PAHs for coal, ranging from 2.0 (anthracite) to 8021 mg/kg (bituminous). 4548 EF P15 for woody materials measured in other countries are mainly for wood logs burned in laboratory chambers, 31, 39, 44, 47 woodstove 18, 36, 3841, 4546, 4951, 54 or fireplace. 18, 3435, 37, 5253 Reported EF P15 values for wood logs burned in laboratory chambers, wood stoves, and fireplaces range from 5.4–35, 1.5–63, and 0.32–332 mg/kg, with geometric means of 15, 8.0, and 16 mg/kg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Kim Oanh et al, (2005) reported emission factors of 16 particle phase PAHs (EF P16 ) for wood in a Chinese clay stove at 1.62 mg/kg [47]. It was also reported that EF P16 for wood chips burned in domestic cooking stoves in other Asian countries ranged in 0.39–5.79 mg/kg with mean and standard derivation of 2.07±1.86 mg/kg [4749]. The results were comparable to that for fuel wood, and obviously lower than that for brushwood in our study.…”
Section: Resultsmentioning
confidence: 99%
“…This could be expected because emissions of PAHs from wood combustion are relatively high compared with those from less clean fuel such as coal briquette and kerosene. 38,39 Wood/vegetative biomass combustion has also been identified as a major source of atmospheric PAHs, 40,41 and is a dominant contributor to the ambient air concentrations of PM and PAHs in certain areas in developed countries where wood is a major heating fuel. 28,25,26 Furthermore, it has been shown in studies that PAH content is higher in wood smoke particles compared with particles from other common sources of ambient air pollution such as traffic and diesel exhaust.…”
Section: Discussionmentioning
confidence: 99%